Family forest owners’ opinions about forest management in northern Finland - Hallikainen, Ville; Hyppönen, Mikko; Pernu, Leena; Puoskari, Jouni (Silva Fennica, 2010)
Forest management guidelines changed at the end of the 1990âs in Finland. Biodiversity, visual landscape, water systems, and different forms of forest use are now better taken into account. The objectives, outdoor recreation motives, and attitudes towards the present forest management activities of the non-industrial private forest owners called family forest owners in this article, whose forest holdings are located in northern Finland, were studied. In addition, a forest owner typology based on the above-mentioned motives, objectives, and attitudes was created, and the relationship between the typology and the forest ownersâ background was tested. Principal component analysis, log-linear models, canonical correlations, and K-means cluster analysis were used in the data analysis. The results showed that especially commercial timber production, but also multiple-use forestry, is important for forest owners. Non-timber products such as game, berries, and forest mushrooms were considered more important than biodiversity, conservation of endangered species, tourism, and reindeer herding. The current, more ecological forest management activities were widely accepted by the owners. The changes had been perceived in the forest management activities. Close relationships were found between the objectives, attitudes and motives of the forest owners. Those owners who emphasized ecological tourism and multiple-use forestry, more frequently accepted detailed conservation and other âsofterâ management methods than those who emphasized commercial timber production. Typologies, called conservationists, timber producers, and multi-objective forest owners, were identified. Forest ownerâs education and source of income were closely related to their typology. Highly educated forest owners and those who gained their money from tourism belonged to the groups named conservationists or multi-objective owners, whereas those who lived on forestry income represented timber producers.